Contending with uncertainty in conservation management decisions. (August 2014) - McCarthy, Michael A.
Abstract : Efficient conservation management is particularly important because current spending is estimated to be insufficient to conserve the world's biodiversity. However, efficient management is confounded by uncertainty that pervades conservation management decisions. Uncertainties exist in objectives, dynamics of systems, the set of management options available, the influence of these management options, and the constraints on these options. Probabilistic and nonprobabilistic quantitative methods can help contend with these uncertainties. The vast majority of these account for known epistemic uncertainties, with methods optimizing the expected performance or finding solutions that achieve minimum performance requirements. Ignorance and indeterminacy continue to confound environmental management problems. While quantitative methods to account for uncertainty must aid decisions if the underlying models are sufficient approximations of reality, whether such models are sufficiently accurate has not yet been examined.